Evaluation of tramadol/paracetamol 75 mg/650 mg combination therapy for early-stage knee osteoarthritis: a retrospective observational study - Alessandro Conforti; Cosimo Ruggiero; Nastasja Palombi; Filippo Messina; Marco Bonifacio; Linda Lucchetti; Marco Ruggiero; Giuseppe La Cava; Roberto Piazza; Mario Mangrella (Reumatismo)
Objective. Knee osteoarthritis (KOA) is a progressive joint disorder that significantly impairs patients’ quality of life. Effective long-term management of KOA remains challenging due to limited pharmacological options and associated adverse effects. This monocentric, retrospective observational study evaluated the efficacy and safety of a fixed-dose tramadol/paracetamol combination (75/650 mg) in alleviating pain in patients with grade I-II KOA according to the Kellgren-Lawrence classification.